Isolation and whole-genome characterization of an emerging G9P[23] porcine rotavirus in Central China - Leng, Chaoliang; Wang, Jiabao; Song, Jiajing; Cao, Jiajia; Jia, Mengtian; Jia, Tianyu; Xiao, Linyue; Zhao, Yingying; Zhang, Yu; Zhang, Jiayin; Zhai, Hongyue; Li, Na; et al. (Frontiers in Veterinary Science, 2025)
Rotavirus (RV), a significant enteric pathogen, causes diarrheal disease in both nursing piglets and infants. To characterize the genomic features and evolutionary patterns of a porcine rotavirus (PoRV) strain, we isolated viral strains from RT-qPCR confirmed PoRV-positive diarrheic piglet specimens through MA104 cell culture inoculation. Viral isolates were definitively characterized through RT-PCR amplification, indirect immunofluorescence assay (IFA), and transmission electron microscopy (TEM), followed by comprehensive whole-genome sequencing and phylogenetic analysis. The results demonstrated successful isolation of a G9P[23] genotype PoRV, designated HN240916. Whole-genome analysis revealed that the genotype constellation was G9-P[23]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Genomic analysis revealed that the NSP3 and NSP5 genes of the HN240916 strain cluster monophyletically with human RVs, while all remaining genes exhibit close phylogenetic affinity to PoRV lineages. The genotype constellation provides genomic evidence of a past interspecies reassortment event between porcine and human RVs. This study expands PoRV molecular epidemiology resources and enables genotype-based prevention strategies.